Evaluation of effects of freezing pretreatment on the grindability, energy consumption and chemical composition of wheat straw. (May 2020) - Lu, Zhaolin; Xie, Tao; Chen, Hao; Li, Leida; Li, Shiyin; Lu, Yao; Hu, Xiaojuan
Abstract: In biomass utilisation, size reduction caused by grinding is a critical procedure because it greatly changes the particle size and shape of the biomass sample, which greatly influences its energy conversion efficiency. Raw biomass is difficult to grind due to its fibrous nature and therefore needs to be pretreated before grinding. Traditional torrefaction pretreatment consumes more energy and changes the chemical composition of biomass. In this study, we select wheat straw with abundant yield in northern China as the biomass sample for testing and introduce a new freezing pretreatment method into the grinding procedure. This method incorporates the freezing of wheat straw with liquid nitrogen. We evaluate the performance of freeze grinding in terms of grindability, energy consumption, chemical composition and energy conversion efficiency, and compare it with that of torrefaction grinding to investigate the effects of pretreatment methods on wheat straw. Particle size and shape distribution are used to characterise grindability. Moreover, we improve sample preparation, image acquisition and segmentation methods to reduce the impact of particle agglomeration. Experimental results demonstrate that freezing as pretreatment improves the grindability and energy conversion efficiency, whilst reducing energy consumption and maintaining chemical composition of wheat straw. Graphical abstract: Image 1 Highlights: Freezing pretreatment enhances the grindability compared with torrefaction. Particle morphology obtained by image analysis represents grindability. Sample preparation is improved to reduce particle agglomeration effect. Freezing grinding consumes less energy than torrefaction grinding. Freezing pretreatment maintains the chemical composition of wheat straw.